ASSET MANAGEMENT BASED ON MANAGEMENT INFORMATION SYSTEM AND ACCOUNTING OF STATE PROPERTY (MANAGEMENT INFORMATION SYSTEMS AND ACCOUNTING FOR STATE PROPERTY) IN THE PUBLIC SERVICE AGENCY (BLU) UNIVERSITAS SEBELAS MARET SURAKARTA - Lelya Fetri Apriliyana; Palikhatun Palikhatun; Payamta Payamta (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
This research was conducted with the aim (1) To determine the implementation of Management Information Systems and Accounting for State Property (SIMAK-BMN) in asset management within the Public Service Agency (BLU) of Universitas Sebelas Maret Surakarta; (2) To find out the advantages of implementing SIMAK-BMN in asset management in the Universitas Sebelas MaretSurakarta; (3) To find out the problems in the implementation of SIMAK-BMN in asset management within the Universitas Sebelas MaretSurakarta; (4) To find out the solution to the problems in the implementation of SIMAK-BMN in asset management within the Universitas Sebelas Maret Surakarta. This research is a qualitative descriptive study. The source of the data came from interviews with 13 informants and related documents. The techniques of collecting data were by interview, observation, and documentation. The sampling technique in the study was purposive sampling. The research subjects in this study were officials and staff related to the management of BMN in Universitas Sebelas Maretwhich were represented by 13 people. Data analysis started from the stage of data collection, data reduction, data display, and conclusion. The results of the study showed that the actual rules regarding BMN Management have not been fully understood by stakeholders in the Universitas Sebelas Maret, this has the effect: the implementation of BMN management is not fully in accordance with applicable regulations; controlling the management of BMN is still weak, so it needs improvement to provide a good understanding of BMN management; currently the stakeholders of BMN management focus more on procurement, while the other management scope is still being ruled out. Keywords: Asset Management, SIMAK-BMN